2015
DOI: 10.1177/1477153515593579
|View full text |Cite
|
Sign up to set email alerts
|

On the calculation and measurement of mean room surface exitance

Abstract: Cuttle has proposed mean room surface exitance as a metric for use within interior lighting design. Two reported barriers to its use are; a lack of available software to calculate the metric and the tedious and cumbersome nature of recording its values in the field using current equipment and methodologies. This paper presents a method for facilitating the calculation of mean room surface exitance using readily available freeware, namely Radiance, and also presents a methodology that utilises high dynamic rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 13 publications
0
36
1
Order By: Relevance
“…Serves as the measure of ambient illumination within an enclosed space. MRSE may be predicted by Duff's precise method, 9 or estimated by Cuttle's formula, [1][2][3] MRSE ¼ FRF=A.…”
Section: Mean Room Surface Exitancementioning
confidence: 99%
See 3 more Smart Citations
“…Serves as the measure of ambient illumination within an enclosed space. MRSE may be predicted by Duff's precise method, 9 or estimated by Cuttle's formula, [1][2][3] MRSE ¼ FRF=A.…”
Section: Mean Room Surface Exitancementioning
confidence: 99%
“…The scope of Duff's studies of exitancebased metrics is extensive. He developed procedures for measurement and calculation; 9 he compared the accuracy of alternative prediction formulae 10 and he conducted experiments which involved subjects making subjective assessments of their surrounding environments. 11,12 The outcomes of these experiments are examined in the following section and are shown to be particularly relevant to this paper.…”
Section: Duff's Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of MRSE attracts much attention and discussion. 5–11 However, the successful adoption of this new concept in lighting applications may largely depend on research advances in the following aspects: (i) experimental evidence of MRSE being clearly linked to people’s assessment of brightness appearance, (ii) an easy way to calculate MRSE, and (iii) a practical method to measure MRSE in the field. For the link between MRSE and brightness appearance, Cuttle 4 has shown that, through subject assessments, MRSE and scene brightness are linearly related.…”
Section: Introductionmentioning
confidence: 99%